The Impact of the First Professional Police Forces on Crime - Anna Bindler; Randi Hjalmarsson (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
This paper evaluates the effect on crime of creating a fundamental modern-day institution: centralized professional police forces tasked with preventing crime. We study the 1829 formation of the London Metropolitan Police - the first professional force worldwide. Using newly digitized and geocoded crime and police data together with difference-indifferences and pre-post designs, we find evidence of a significant reduction in violent crimes (despite the possibility of off-setting increases in clearance and reporting rates). In contrast, a reduction in property crime is not visible.
Keywords: K42; N93; H0; 330; police; crime; deterrence; economic history; institutions